2022
DOI: 10.3389/fcvm.2022.965512
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance imaging patterns of acute COVID-19 mRNA vaccine-associated myocarditis in young male patients: A first single-center experience

Abstract: BackgroundThe risk of myocarditis after mRNA vaccination against COVID-19 has emerged recently. Current evidence suggests that young male patients are predominantly affected. In the majority of the cases, only mild symptoms were observed. However, little is known about cardiac magnetic resonance (CMR) imaging patterns in mRNA-related myocarditis and their differences when compared to classical viral myocarditis in the acute phase of inflammation.Methods and resultsIn total, 10 mRNA vaccination-associated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Collaborating previously published findings, we found vaccine associated myocarditis to predominantly affect younger males (1,3,35). Typically, clinical course of disease is mild with rapid resolution of symptoms within a few months (17,19,25,28,33), although persistent LGE on CMR indicative of fibrous scar tissue was noted in all our patients. Resolution of other CMR findings (elevated T1 and T2 times, focal or diffuse edema) are to be expected as the extent of the inflammatory process diminishes over time.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Collaborating previously published findings, we found vaccine associated myocarditis to predominantly affect younger males (1,3,35). Typically, clinical course of disease is mild with rapid resolution of symptoms within a few months (17,19,25,28,33), although persistent LGE on CMR indicative of fibrous scar tissue was noted in all our patients. Resolution of other CMR findings (elevated T1 and T2 times, focal or diffuse edema) are to be expected as the extent of the inflammatory process diminishes over time.…”
Section: Discussionsupporting
confidence: 88%
“…The start of the coronavirus disease-19 (COVID- 19) outbreak caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the end of 2019 prompted a world-wide effort to curtail the spread of the pandemic. One possible way to achieve this was the development of safe and effective vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an extensive body of literature on CMR findings in all these syndromes that showed different patterns of myocardial pathology such as global myocardial edema, irreversible myocardial injury such as necrosis and scarring, as well as pericardial effusion. Several such studies have reported similarities of such patterns to those found in myocardial inflammation triggered by other viruses (4,5), albeit with some difference in some studies (6,7).…”
Section: Introductionmentioning
confidence: 83%